Percepções de um grupo de professores do ensino médio sobre a ideia de "bom" e "mau" aluno na cidade de São Carlos - SP - Rossini, Thais de Freitas (2020)
This work’s main goal is to analyse aspects that bases the “good and bad” idea that a group of high school teachers have about their students, in order to comprehend in which notions (social, moral, pedagogic, etc.) these conceptions are grounded. As specific objectives, observing in which form this classification is enunciated and if there are evidences for the “Gift Theory” among this conceptions. It was applied in the discussion some concepts from the sociologist Pierre Bourdieu as of habitus, the field and the teacher judgement. The data collect develop in two steps, first with the sent of an online questionnaire by e-mail and later via a semi structured interview, both with high school teacher active in the city of São Carlos, SP. The online quiz received sixteen answers and seven were the interviews performed. The data were analysed based on content analysis. The data from the quiz as well as the interviews were analyzed in conjunction, being then organized in three analysis categories: the good student, the bad student and the effects of classification in the evaluation. It was possible to perceive that the idea of good student is based on effort and the appreciation of merit, the idea of bad student is connected to disinterest and comments over Family and social background. Even the practice analysis in classroom has not been looked on in the field work, as the teacher describe the form he evaluates the students, it is clear the path through which the classification between good and bad students can be noted objectively through the evaluation criteria.